Comparative Study on the Growth and Yield of Ganoderma lucidium Mushroom Cultivated on African Peach (Nauclea diderrichii) and Bush Mango (Endospermum medullosum) Sawdust as Substrates - S Fakoya; T. J. Adedayo (International Journal of Fungi, 2025)
This study was conducted to find out which substrate provides for the best artificial development of G. lucidium. Mango (Mangifera indica) leaves were added to the saw dusts of Nauclea diderrichii and Endospermum medullosum, which were both utilized as substrates for growing. The substrates were inoculated with Ganoderma spawn and then exposed and hydrated to start the fruiting process. Three replications of the process were carried out. It was observed that E. medullosum supported the growth and good yield of the mushroom by taking 7 days to commence ramification, 37 days to achieve complete ramification, and 68 days for harvesting. Due to the slowed mycelial growth, N. diderrichii was unable to promote the harvesting and ring formation of G. lucidium. As a result, it cannot be advised to use N. diderrichii sawdust as a substrate for the growth of G. lucidium. On the other hand, the mushroom proliferated well in the E. medullosum substrate producing fully grown Ganoderma mushroom in a short time compared to other studies that used different substrates other than E. medullosum. Considering the results of this study, E. medullosum supplemented with Mango (Mangifera indica) leaves is recommended as a suitable substrate for the cultivation of G. lucidium.
Keywords: Ganoderma lucidium; Yield; growth; medicinal mushroom; substrate